PERBANDINGAN HASIL BELAJAR SISWA YANG DIAJAR DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DENGAN TIPE STUDENTS TEAMS ACHIEVEMENT DIVISION (STAD) PADA MATERI BANGUN DATAR PERSEGI - Mara Samin Lubis (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
This study aims to determine differences in learning outcomes between students taught by cooperative learning model type TGT with students taught by STAD type cooperative learning model in class VII MTs PAB 2 Sampali, as well as to compare the average of learning outcomes of students who were taught by the model of learning cooperative type TGT with students who are taught by STAD type cooperative learning model in class VII MTs PAB 2 Sampali on square flat matter. This type of research is a quantitative research using comparative analysis. This research is a study of population consisting of all students of class VII MTs PAB 2 Sampali academic year 2016/2017. The sample is obtained by taking two classes, namely class VII-2 which will be given teaching method of TGT and VII-3 which will be given STAD teaching method which each class is 21 students. Analyze the difference of learning result using t-test (t-test seperated variance), while the mean comparison of learning result using t-test polled variance. These findings show: 1). The value of t arithmetic for the first hypothesis test = 5.696 with t table at 5% significance level = 1.684. 2). The value of t arithmetic for the second hypothesis test = 6.292 with t table at 5% significance level = 1.684. 3). The conclusion of this study explains that there are differences in student learning outcomes taught by cooperative learning model type TGT with students taught by STAD type cooperative learning model, and the average of student learning outcomes taught by cooperative learning model TGT type is greater than the average. average learning outcomes of students who were taught by STAD type cooperative learning model on square flat matter in class VII MTs PAB 2 Sampali